A multi-organizational cross-sectoral collaboration: empirical evidence from an 'Empty Homes' project. Issue 1 (2nd January 2016) - Gillett, Alex; Loader, Kim; Doherty, Bob; Scott, Jonathan M.
Abstract : This paper analyses the processes, outcomes and tensions of a cross-sectoral collaborative venture involving several organizations with multiple logics and is based on empirical evidence from a collaborative 'Empty Homes' project. While, paradoxically, multiple logics are a basis for the partnership's existence (for example 'value for money' and local community benefit) to achieve these different aims simultaneously, its other aims or logics at times conflicted, resulting in intra-partnership tensions. Hence we offer novel insights into the practical aspects of collaboration at a local level and on multi-organizational relationships.